Desenvolvimento de filmes comestíveis à base de galactomananas vegetais para conservação de frutos - Lima, Álvaro Marcos Pereira (2009)
Great losses (25 to 80%) in the quality of fresh fruits occur between their harvest and consumption. A limiting factor in the distribution chain of these foods is their short shelf life. This fact creates a lot of economic waste in developed countries, and in tropical countries assume devastating proportions. The use of film-based coating natural galactomannans, nontoxic and eatable can bring economic benefits in increasing the shelf life of perishable fruits and more environmental because it is a biodegradable material. The objective of this work was to produce different edible coatings from galactomannans otained in leguminosae seeds (Adenanthera pavonina and Caesalpinia pulcherrima) looking for his use in order to increase shelf life of fruits. Having also as a complementary part to evaluate the ability of these galactomannans in forming blends with collagen, and analyze the characteristics of the films formed from these blends. Filmogenic solution of galactomannan and glycerol were prepared by varying the concentration of galactomannan from 0.5% to 1.5% and glycerol concentrations ranging from 1% to 2%. The films were evaluated with respect to their wettability (Ws), eight films were selected from A. pavonina which showed higher values of Ws for each fruit and studied four C. pulcherrima films. These films were tested for permeability to water vapor, 02 and CO2 . For the first two, higher concentrations of galactomannan reduced permeability, as well as the use of lower concentrations of glycerol. For the permeability to carbon dioxide is the opposite: higher concentrations of glycerol reduces PCO2. The films showed good mechanical properties such as elasticity and considerable tensile strength, compatible with other films of polymers previously studied. Based on the criteria - the highest values of the wettability, lower values of permeability to water vapor, the lower values of oxygen permeability and lower values of permeability to carbon dioxide - the following film formulations were more appropriate for each fruit: acerola - 0.5% A. pavonina galactomannan and 1% glycerol; caja - 1% of A. pavonina galactomannan and 1% glycerol; mango and pitanga - 1.5% of A. pavonina galactomannan and 1% glycerol and seriguela- 0.5% C. pulcherrima galactomannan and 1.5% glycerol. Galactomannan-collagen-glycerol blends were also studied regarding the same properties, with the objective of improving mechanical and barrier characteristics of these films. Were selected in terms of Ws the best blend to coat mango (0.5% of A. pavonina galactomannan, 1.5% collagen and 1.5% glycerol) and best blend to coat apple (0.5% of C.pulcherrima galactomannan, 1.5% collagen and without glycerol). The blend of galactomannan of C. pulcherrima - collagen was less permeable to water vapor and more permeable to 02 and CO2. Mangoes were coated with the A.Pavonina - collagen - glycerol blend and the rate of gas transfer was compared with uncoated mangoes. Was observed a 28% lower consumption of 02 and a 11 % lower production of CO2. The same procedure was repeated for apples (this time using the blend of C. pulcherrima).The CO2 produced and 02 consumed was approximately 50% lower in coated apples to apples comparison without the coating.